Sound radiation by a hollow circular elastic cylinder rotated in water with a variable angular velocity - Piddubniak, O. P.; Piddubniak, N. G. (Archives of Acoustics, 2003)
In this paper the sound radiation from an elastic circular cylinder of infinite length rotated with a non-uniform angular velocity in water is studied. The cylinder is empty inside. Exact solutions of the equations which describe the hydroelastic interaction are obtained using the Fourier transform over time. Numerical examples show that the spectral structure of the sound radiation from an elastic tube is more complicated than that of a solid cylinder. In particular, the resonances of this structure are essentially dependent on the thickness of the rotating object and are subject to the phenomena of dispersion.